Disparities in pre‐eclampsia and eclampsia among immigrant women giving birth in six industrialised countries. (24th April 2014) - Urquia, ML; Glazier, RH; Gagnon, AJ; Mortensen, LH; Nybo Andersen, A‐M; Janevic, T; Guendelman, S; Thornton, D; Bolumar, F; Río Sánchez, I; Small, R; Davey, M‐A; et al.
<x xml:space="preserve">Abstract</x> Objective To assess disparities in pre‐eclampsia and eclampsia among immigrant women from various world regions giving birth in six industrialised countries. Design Cross‐country comparative study of linked population‐based databases. Setting Provincial or regional obstetric delivery data from Australia, Canada, Spain and the USA and national data from Denmark and Sweden. Population All immigrant and non‐immigrant women delivering in the six industrialised countries within the most recent 10‐year period available to each participating centre (1995–2010). Methods Data was collected using standardised definitions of the outcomes and maternal regions of birth. Pooled data were analysed with multilevel models. Within‐country analyses used stratified logistic regression to obtain odds ratios (OR) with 95% confidence intervals (95% CI). Main outcome measures Pre‐eclampsia, eclampsia and pre‐eclampsia with prolonged hospitalisation (cases per 1000 deliveries). Results There were 9 028 802 deliveries (3 031 399 to immigrant women). Compared with immigrants from Western Europe, immigrants from Sub‐Saharan Africa and Latin America & the Caribbean were at higher risk of pre‐eclampsia (OR: 1.72; 95% CI: 1.63, 1.80 and 1.63; 95% CI: 1.57, 1.69) and eclampsia (OR: 2.12; 95% CI: 1.61, 2.79 and 1.55; 95% CI: 1.26, 1. 91), respectively, after adjustment for parity, maternal age and destination country. Compared with native‐born women, European and East Asian immigrants were at lower risk in most industrialised countries. Spain exhibited the largest disparities and Australia the smallest. Conclusion Immigrant women from Sub‐Saharan Africa and Latin America & the Caribbean require increased surveillance due to a consistently high risk of pre‐eclampsia and eclampsia.